Pengaruh Investasi terhadap Produksi Pangan di Indonesia - Ginting, Hezkya Refienes (Jurnal Pendidikan Indonesia, 2025)
This study aims to analyze the impact of investment on food production in Indonesia from 2000 to 2022. Food production reflects a country's ability to provide sufficient and nutritious food, where investment can support it through efficient agricultural technology and the development of distribution infrastructure. The data includes the Food Production Index (FPI), Domestic Investment (PMDN), and Foreign Investment (PMA) in the food sector, inflation, economic growth, and population. Panel data regression methods using Ordinary Least Squares (OLS) were applied to evaluate the relationships among variables. The results show that PMA, PMDN, and inflation positively affect FPI at a 10% significance level, highlighting the importance of investment and price stability. Conversely, economic growth and population have no effect. These findings emphasize the importance of investment policies in strengthening food production.